A Research Study on the Effective Power Reception Area of One-to-Many Wireless Power Transfer Systems - Ke Guo; Xinyue Zhang; Yi Yang; Jiahui Li; Zeyang Liu (World Electric Vehicle Journal)
In multi-load wireless power transfer (WPT) systems, when multiple loads simultaneously charge using the same transmitter, the unpredictable spatial positions of the loads and the presence of cross-coupling make it challenging to achieve complete system decoupling, thereby limiting the effective power reception area. To address this issue, this paper investigates a one-to-multiple WPT system based on a single-transistor P#-type LCC-S compensation network. Air-core coils are employed at the receiving end to mitigate cross-coupling, and the effective power reception area is analyzed. First, the operating principle of the system is examined and the parameter configuration conditions for the resonant circuit are derived. Then, MATLAB/Simulink R2022b is used to establish simulation circuit models for both single-transmitter single-receiver and single-transmitter dual-receiver WPT systems. The results indicate that for an effective output power of 5 W, the mutual inductance ranges are (3.5, 6) μH and (3, 6.5) μH, respectively. Next, finite element simulations are conducted to analyze the mutual inductance variations caused by spatial misalignment of the coils. For the single-transmitter single-receiver system, when the transmission distance is 5–12.5 mm, the effective power reception area corresponds to an X- and Y-axis misalignment of ±15 mm, while at a transmission distance of 10 mm, the effective reception area is ±10 mm along both axes. In the single-transmitter dual-receiver system, for a transmission distance of 5–14 mm, the maximum reception area is ±15 mm along the X-axis and ±10 mm along the Y-axis. Finally, an experimental platform is built to verify that multiple loads at different positions can achieve effective power reception for charging.